Transfusões sanguíneas em hepatectomias realizadas no Hospital Universitário João de Barros Barreto - PORCIÚNCULA, Juliana Maria Corrêa da (2022)
INTRODUCTION: the indications for hepatectomy are increasing due to greater safety in performing this procedure, but also because the early diagnosis of benign or malignant liver lesions favored by introductory radiological armamentarium. OBJECTIVE: To evaluate the interference of blood transfusion in patients who underwent hepatectomy at the Hospital Universitário João de Barros Barreto (HUJBB). MATERIAL AND METHODS: we performed a descriptive cross-sectional retrospective observational study ad individual with 36 patients who underwent liver resection HUJBB in January 2000 to December 2010. RESULTS: On the records examined, 66,67% were female, while 33,33% were male; 22,22% were 51 to 60 years old and 30,56% had more than 60 years of age, it turns out that 63,89% underwent segmentectomy, 19,44% right hepatectomy, 13,89% left hepatectomy and 2,78% the left trissegmentectomia, were 69,44% were malignat and 30,56% were benign; about the complications of intra-operative the hypovolemic shock were 8,33% and 2,78% damage to inferior vena cava; in relation to complications after surgery, 11,11% had pneumonia and sepsis, 2,78% have hadbuttock abscess, subphrenic abscess, anasarca, pleural effusion, dyspnea, biliary fistula, hypothermia and urinary tract infection, 44,44% received one to three bags of red blood cells, 22,22% from four to six bags; were 22,22% one to three bags of fresh frozen plasma, 5,56% four to six bags, 5,56% of seven to nine bags and 2,78% received a transfusion of ten or more bags of fresh frozen plasma during the hospitalization; 66,67% of patients not died and 33,33% died. CONCLUSION: The relationship of red cell concentrate transfusion complications and intra-and postoperative, it was observed that 75,76% and 75.00% respectively, were transfused but had no complications. In relationship of fresh frozen plasma and complications during and after surgery, 69.70% and 70.00% respectively, were not transfused and had no complications. There were 33.33% of deaths, and the leading causes of death were septic shock in 33.33% cases and 25.00% in hypovolemic shock.